Efektifitas Pelatihan Asuhan Keperawatan pasien Kanker Payudara dalam Penerapan SDKI, SLKI, dan SIKI - Zuriati Zuriati; Imelda Avia; Nurleila Nurleila; Atik Rachmawati (Universitas Pahlawan Tuanku Tambusai, 2022)
Nursing documentation is the most important part of providing nursing care given by nurses to patients, especially for breast cancer. This community service activity is aimed at increasing the knowledge of nurses in providing nursing care and documenting by the guidelines from the Indonesian National Nurses Association (PPNI), namely 3S: Indonesian Nursing Diagnosis Standards (IDHS), Indonesian Nursing Outcomes Standards (SLKI) and Indonesian Nursing Intervention Standards (SIKI). ). This training is provided online, which begins with a pre-test, then lectures and discussion/problem-based solving followed by a post-test. Participants in this training were all student nurses and nurses with a total of 285 participants. The results of this training found an increase in knowledge of the application of the 3S covering signs and symptoms, diagnoses, interventions, and outcomes. It is hoped that from the results of this activity nurses have started to implement nursing care and document it using this 3S.